Synergistic cytotoxicity of Solanum aculeastrum with 4-hydroxytamoxifen in the MCF-7/TAMR-1 breast adenocarcinoma cell line - Cordier, Werner (University of Pretoria, 2024)
Dissertation (MSc (Pharmacology))--University of Pretoria, 2024.